The Effective Participation of a Clinical Pharmacist in Detecting Medication Errors in the COVID-19 Intensive Care Unit - Dena Firouzabadi; Seyed Mohammad Hosseini Saadi; Negar Firouzabadi (Shiraz University of Medical Sciences, 2023)
With the emergence of the COVID-19 pandemic, a large number of patients required hospitalization and intensive care unit admissions. Patients with pre-existing medical conditions were associated with a higher chance of severe disease. On the other hand, medication errors in part resulting from polypharmacy are commonly observed in hospitalized patients. At the time of the Delta variant peak and the high influx of COVID-19 patients to the hospitals, clinical pharmacy ICU ward rounds were implemented to detect, and prevent medication errors to improve patient safety and care. Patients with known COVID-19 infection that were admitted to the ICU for a duration of 4 months were included in this prospective study. Every day (Saturday to Thursday) ICU patient rounds was performed by the clinical pharmacist. Medication reconciliation was done for all patients to detect probable drug omission or duplication during admission. Pharmaceutical Care Network Europe Foundation (PCNE) classification was used for classifying drug-related problems. A total of 86 patients were evaluated for medication errors during ICU admission. A total of 398 drug-related comments were given and 90% of the interventions were accepted by the attending physician. The most common medication error was attributed to overdosage of medications, mostly glucocorticoid therapy. The survival rate amongst patients was 56.1%. Clinical pharmacy interventions and medication reconciliation at times of pandemics can help towards improvement of clinical practice, patient safety, and saving of medication resources. Early detection of medication errors by clinical pharmacists can prevent further patient complications and death.